(untitled) (Journal of Human Sciences, 2025)
The current research aims to identify the psychological pressure of the perpetrators of the crime of imprisoned in the Security Directorate of Sebha City And the detection of the level of psychological stress among the sample members, The research included a sample consisting of (100) the perpetrator of the murder, choose structure of the sacrifice sample, The researcher followed the descriptive analytical method, And I used the psychological pressure scale for the prisoner, prepared by Samira Hodour, The search results found: The high level of psychological stress among a sample of murder criminals imprisoned in the Sebha Security Directorate, There are no statistically significant differences in the psychological pressure of the imprisoned perpetrators of the crime of murder in the director of security in Sebha city due to the age variable, There are no statistically significant differences in the psychological pressure of the perpetrators of the crime of murder due to the variable length of imprisonment, There are statistically significant differences in the psychological pressure of the perpetrators of the murder due to the variable number of times entering prison and in favor of the first time the killer enters prison.